2015
DOI: 10.19030/jaese.v2i2.9513
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Individual Test Of Astronomy STandards (TOAST) Item Responses

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 29 publications
1
9
0
5
Order By: Relevance
“…Pirst. although everybody has experience with the apparent motion of the Sun, several studies have shown that many people cannot really explain this phenomenon [13][14][15][16]. Moreover.…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 99%
“…Pirst. although everybody has experience with the apparent motion of the Sun, several studies have shown that many people cannot really explain this phenomenon [13][14][15][16]. Moreover.…”
Section: Published By the American Physical Society Under The Terms Omentioning
confidence: 99%
“…Başarı testi için her bir kazanıma yönelik en az bir tane soru içeren 31maddelik bir soru havuzu hazırlanmıştır. Soru havuzunda yer alan sorular; daha önce astronomi konularında araştırma yapan (Arıcı, 2013;Demirçalı, 2016;Baltacı, 2013;Bailey, 2012;Gündoğdu, 2014;Öz, 2004;Slater, 2015;Taşcan, 2013;Trumper, 2001;Trumper, 2006;Türk, 2015;Wallace, 2011;Yılmaz 2014)…”
Section: Kapsam Geçerliğiunclassified
“…Ayrıca Dünya ve Evren konu alanıyla ilgili alan yazın incelendiğinde, çalışmaların büyük bölümünün Dünya, Güneş, Ay, Evren ve Mevsimler konularına ilişkin meteor ve göktaşı, yıldızlar, yıldız kayması, kuyruklu yıldız, güneş, gezegen, gel git olayı, uzay, gökada, evren, astronomi birimi (AB), ışık yılı, uzay kirliliği kavramları ile ilgili öğrencilerin kavram yanılgılarını ve zihinsel modellerini belirlemeye yönelik olduğu tespit edilmiştir. İncelenen bu çalışmalarda farklı öğrenci seviyelerine yönelik, birbirinden farklı astronomi kavramlarını içeren başarı testleri geliştirildiği görülmüştür (Baloğlu Uğurlu, 2005;Bailey, Prather & Slater, 2012;Bektaşlı, 2013;Bektaşlı, 2016;Bostan, 2008;Ekiz, & Akbaş, 2005;Kurnaz & Değirmenci, 2012;Slater, Schleigh, & Stork, 2015;Trumper, 2001;Türk, Alemdar & Kalkan, 2012;Wallace, 2011). Bu çalışmalarda çoktan seçmeli testler ile çeşitli öğrenim kademelerindeki öğrencilerin bilgi düzeyleri, zihinsel modelleri, kavram yanılgıları ortaya konmuştur.…”
Section: Tartışma Ve Sonuçunclassified
See 1 more Smart Citation
“…¼ 120 possible different responses, while a 10-item task allows a total of 3.6 × 10 6 possible different responses, with each task having only one correct solution. (If students are constrained to a MCQ format for ranking tasks, they may typically be limited to only four or five possible responses; cf., e.g., Slater et al [26]) Thus, despite their apparent simplicity, such ranking tasks can lead to a very broad spectrum of responses, from which a wealth of potentially interesting data may be extracted.…”
Section: B Ranking Tasksmentioning
confidence: 99%